Brain abscess and bronchopneumonia caused by Acinetobacter baumannii in a 2-year-old female sheep - Eroksuz, Yesari; Otlu, Baris; Eroksuz, Hatice; Gursoy, Nafia Canan; Yerlikaya, Zeynep; Incili, Canan Akdeniz; Timurkan, Mehmet Ozkan (Taylor & Francis Ltd, 2018)
[Abstract Not Available]
Keywords: Sheep; ovine; Acinetobacter baumannii; brain abscess; pneumonia